GSG2 knockdown suppresses cholangiocarcinoma progression by regulating cell proliferation, apoptosis and migration - Zhou, Jun (Oncol Rep, 2021)
Cholangiocarcinoma (CCA) is the second most common type of hepatocellular carcinoma characterized by high aggressiveness and extremely poor patient prognosis. The germ cell-specific gene 2 protein (GSG2) is a histone H3 threonine-3 kinase required for normal mitosis. Nevertheless, the role and mechanism of GSG2 in the progression and development of CCA remain elusive. In the present study, the association between GSG2 and CCA was elucidated. Firstly, we demonstrated that GSG2 was overexpressed in CCA specimens and HCCC-9810 and QBC939 cells by immunohistochemical (IHC) staining. It was further revealed that high expression of GSG2 in CCA had significant clinical significance in predicting disease deterioration. Subsequently, cell proliferation, apoptosis, cell cycle distribution and migration were measured by MTT, flow cytometry, and wound healing assays, respectively in vitro. The results demonstrated that downregulation of GSG2 decreased proliferation, promoted apoptosis, arrested the cell cycle and weakened migration in the G2 phase of CCA cells. Additionally, GSG2 knockdown inhibited CCA cell migration by suppressing epithelial-mesenchymal transition (EMT)-related proteins, such as N-cadherin and vimentin. Mechanistically, GSG2 exerted effects on CCA cells by modulating the PI3K/Akt, CCND1/CDK6 and MAPK9 signaling pathways. In vivo experiments further demonstrated that GSG2 knockdown suppressed tumor growth. In summary, GSG2 was involved in the progression of CCA, suggesting that GSG2 may be a potential therapeutic target for CCA patients.